Implementation of a MIMO system for Wireless Power Transfer Using Acoustic Approach - Thoriq Zaid; Shakir Saat; Norezmi Jamal; Siti Huzaimah Husin; Yusmarnita Yusof; SK Nguang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents a development of Acoustic energy transfer (AET) system through the air medium by implementing a Multiple Input-Multiple Output (MIMO) arrangement of transducers to transmit energy. AET system allows power to be transmitted without wire connection. The MIMO system is proposed in this paper to increase the efficiency of the transmitting power by multiplying the received power. The simulation and experimental works are carried out using a Class E power converter and the obtained results are analyzed accordingly. Based on the experimental results, the 18.57mW output power is obtained at 40kHz operating frequency when triple transducer is used. It  contributes to 30.96% efficiency to the power transfer system.